2012
DOI: 10.1021/es204489h
|View full text |Cite
|
Sign up to set email alerts
|

Choline-Based Ionic Liquids-Enhanced Biodegradation of Azo Dyes

Abstract: Industrial wastewaters such as tannery and textile processing effluents are often characterized by a high content of dissolved organic dyes, resulting in large values of chemical and biological oxygen demand (COD and BOD) in the aquatic systems into which they are discharged. Such wastewater streams are of rapidly growing concern as a major environmental issue in developing countries. Hence there is a need to mitigate this challenge by effective approaches to degrade dye-contaminated wastewater. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 25 publications
0
44
0
1
Order By: Relevance
“…27, was also observed. However, the authors report that with the amide in the C2 (89,90,91), C4 (79) or C4,5 (92) low biodegradation in the range 2-17% was observed. This observation is in contrast to the increase in biodegradability observed when modifying some pyridinium ILs to nicotinium ILs, see Section 4.3.1.3.…”
Section: View Article Onlinementioning
confidence: 99%
“…27, was also observed. However, the authors report that with the amide in the C2 (89,90,91), C4 (79) or C4,5 (92) low biodegradation in the range 2-17% was observed. This observation is in contrast to the increase in biodegradability observed when modifying some pyridinium ILs to nicotinium ILs, see Section 4.3.1.3.…”
Section: View Article Onlinementioning
confidence: 99%
“…Due to all the outstanding properties of cholinium-based ionic liquids, scientific interest in them has increased in the past few years, with applications as diverse as crosslinking agents for collagen-based materials, 18 in the pretreatment and dissolution of biomass, 16,19 in improving the visualization of hydrous samples by scanning electron microscopy, 20 and use as cosubstrates for microorganisms in the degradation of azo dyes. 21 Moreover, a number of works have described novel cholinium-based ionic liquids in which the protein structure and enzyme function can be maintained or even increased. 14,22 The work of Deive et al 23 has shown that fungi are more able to grow (compared to bacteria) during their exposure to these biocompatible ionic liquids and evaluated the ionic liquid degradation during cultivation.…”
Section: -16mentioning
confidence: 99%
“…Various technologies have been developed to solve this problem, such as adsorption, 17 coagulation/flocculation, 18 oxidation, 19 photodegradation, 20 membrane filtration 21 and the harnessing of biological processes. 22 Pollutant remediation via adsorption processes is considered to be one of the most promising techniques owing to operation simplicity, high efficiency and applicability for the treatment of wastewater on a large scale. 23 In addition to the traditional activated carbon, 24 different types of adsorbent materials have been developed, such as natural or synthetic zeolites, 25 organically modified porous silica, 26 natural or modified clays 27 and macroporous polymeric adsorbents.…”
Section: Introductionmentioning
confidence: 99%